Fundamentals of bio-based technologies for selective metal recovery from bio-leachates and liquid waste streams - Sieber, Anna; Spiess, Sabine; Rassy, Wadih Y.; Schild, Dominik; Rieß, Thomas; Singh, Shalini; Jain, Rohan; Schönberger, Nora; Lederer, Franziska; Kremser, Klemens; Guebitz, Georg M. (Frontiers in Bioengineering and Biotechnology, 2025)
The number of metal-containing waste streams resulting from electronic end-of life products, metallurgical by-products, and mine tailings to name but a few, is increasing worldwide. In recent decades, the potential to exploit these waste streams as valuable secondary resources to meet the high demand of critical and economically important raw materials has become more prominent. In this review, fundamental principles of bio-based metal recovery technologies are discussed focusing on microbial metabolism-dependent and metabolism-independent mechanisms as sustainable alternatives to conventional chemical metal recovery methods. In contrast to previous reviews which have partially addressed this topic, a special focus will be given on how fundamental principles of bio-based recovery technologies can influence the selectivity and specificity of metal recovery. While conventional methods for metal recovery show benefits in terms of economic affordability, bio-based recovery technologies offer advantages in terms of efficiency and environmentally friendliness. Modifications and adaptations in the processes of biosorption, bioaccumulation and bioelectrochemical systems are highlighted, further emphasizing the application of metal-binding peptides and siderophores to increase selectivity in the recovery of metals. Single metal solutions or mixtures with a low complexity have been the focus of previous studies and reviews, but this does not reflect the nature of complex industrial effluents. Therefore, key challenges that arise when dealing with complex polymetallic solutions are addressed and the focus is set on optimizing bio-based technologies to recover metals efficiently and selectively from bio-leachates or liquid waste streams.